Oregano Oil and Harmless Blue Light to Synergistically Inactivate Multidrug-Resistant Pseudomonas aeruginosa - Lu, Min; Wong, Ka Ioi; Li, Xin; Wang, Fei; Wei, Li; Wang, Shen; Wu, Mei X. (Frontiers in Microbiology, 2022)
Blue light (BL) at 405 nm and oregano essential oil (OEO) have shown bactericidal activity by its own. Here, we demonstrated that the two synergistically killed multidrug-resistant (MDR) Pseudomonas aeruginosa (Pa). Pa ATCC19660 and HS0065 planktonic cells and mature biofilms were reduced by more than 7 log10 after treatment by BL combined with OEO, in sharp contrast to no significant bacterial reduction with the monotreatment. The duo also sufficiently eliminated acute or biofilm-associated infection of open burn wounds in murine without incurring any harmful events in the skin. The synergic bactericide was attributed mainly to the ability of OEO to magnify cytotoxic reactive oxygen species (ROS) production initiated by BL that excited endogenous tetrapyrrole macrocycles in bacteria while completely sparing the surrounding tissues from the phototoxic action. OEO ingredient analysis in combination with microbial assays identified carvacrol and its isomer thymol to be the major phytochemicals that cooperated with BL executing synergic killing. The finding argues persuasively for valuable references of carvacrol and thymol in assessing and standardizing the bactericidal potential of various OEO products.